Memotret Paradigma Keberagamaan Kaum Santri - M. ULINNUHA KHUSNAN (Jurnal Dialog, 2017)
Santri has been the first entity of Islamic education that contributed a lot to the independent proscees and the exixtance of this nation. In doing the significant role, santri groups have had variety of religious paradigm. Some had normative, fundamentalis, exclusive and conservative paradigm. But others had actualis, inclusive, contextualis, rasionalis and liberalis paradigm. This article potrayed the typology of santri’s paradigm.